Design of a Modern Web-Based Mail Management Information System Using the Prototype Model at PT Kalimantan Teknologi Indonesia - Maulana, Reza; Mukti, Aditya; Firmansyah, Yoki; Purwaningtias, Deasy (Yayasan Kita Menulis, 2026)
PT Kalimantan Teknologi Indonesia manages its incoming and outgoing mail using a conventional manual approach, which often results in inefficiency, loss of documents, and difficulties in information retrieval. This study aims to design a web-based mail management information system that enhances the efficiency, accuracy, and traceability of administrative correspondence. The research adopts the Prototype development methodology, consisting of requirement analysis, system design, prototype creation, and evaluation. Data were collected through interviews, observations, and document analysis to identify user needs and administrative workflows. The system was developed using Figma employed for interface prototyping. The resulting system provides features for digital recording, classification, searching, and reporting of both incoming and outgoing mail. Testing results indicate that the prototype effectively reduces administrative workload, improves data accuracy, and accelerates document tracking. This study demonstrates that a well-structured digital correspondence system can serve as a foundation for administrative transformation in small and medium-sized enterprises.